Hydrology days award - Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2011)
The 2011 Hydrology Days Award was presented to W. James Shuttleworth.
Hydrology days 2011
AGU hydrology days 2011
2011 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2011.
Keywords: Hydrology -- Congresses; Award winners